KOMUNIKASI ANTARPRIBADI ORANGTUA DAN GURU DALAM MEMAHAMI PENDIDIKAN INKLUSI DI TK JASMIEN JAKARTA UTARA - Nilamsari, Natalina (JURNAL PUSTAKA KOMUNIKASI, 2018)
Education is the basic right of Indonesian people include children with special needs (ABK). Understanding of inclusive education for kindergarten is important for parents and teachers. Interpersonal communication can be a bridge to share ideas, facts, knowledge, thoughts from parents and teachers about inclusive education at Jasmien Kindergarten in North Jakarta. This is a descriptive qualitative research with case study method. The data obtained byobservation indepth interviews with the parents both of ABK and non ABK also the teachers. The study was conducted in May-July 2017. The result shows that the understanding of inclusive education for parents sourced by the experience the children in inclusion school. ABK and not ABK grow well by playing, learning and interact among the children. For teachers, inclusion education is a tangible form of fulfillment of the basic rights of children. Interpersonal communication between parents and teachers is found in dimensions: openness, empathy, supportive, positiveness and equality.